Implantable Cardioverter Defibrillator Shocks and Psychological Distress: Examining the Mediating Roles of Implantable Cardioverter Defibrillator–Related Concerns and Perceived Control. Issue 1 (January 2020) - Lee, Kyoung Suk; Kim, Jun Hyung; Kang, Ki-Woon; Miller, Jennifer; McEvedy, Samantha M.; Hwang, Seon Young; Moser, Debra K.
Abstract : Background: Although the implantable cardioverter defibrillator (ICD) has a survival benefit for the prevention of sudden cardiac death, ICD recipients commonly experience emotional distress as a consequence of ICD shocks. Objective: The aim of this study was to examine whether the association between ICD shocks and psychological distress (anxiety and depressive symptoms) is mediated by ICD-related concerns and perceived control among ICD recipients. Methods: This was a multinational cross-sectional observational study of 334 ICD recipients. Patients reported the number of shocks received since ICD implantation and completed questionnaires to assess anxiety, depressive symptoms, ICD-related concerns, and perceived control. A path analysis was conducted to explore the relationship of receiving ICD shocks with anxiety and depressive symptoms and the mediating effects of ICD-related concerns and perceived control. Results: Of the 334 ICD recipients, 39.2% experienced ICD shocks at least once since implantation. There was no direct effect of ICD shocks on anxiety and depressive symptoms. Experiencing ICD shocks was indirectly associated with an increased likelihood of anxiety and depressive symptoms via the pathways of ICD-related concerns and perceived control (indirect effects on anxiety = 0.060, 0.043; indirect effect on depressive symptoms = 0.025, 0.073). Conclusion: Experiencing defibrillator shocks was associated with psychological distress in ICD recipients; the relationship was fully mediated by ICD-related concerns and perceived control. These results suggest that clinicians should routinely assess ICD-related concerns and perceived control in patients with ICD. Research is needed to develop and test interventions to decrease emotional distress related to the ICD shock experience.